1965
DOI: 10.1152/jappl.1965.20.2.202
|View full text |Cite
|
Sign up to set email alerts
|

Motor control of pulmonary airways studied by nerve stimulation

Abstract: To investigate the motor control of the pulmonary airways we combined electrical stimulation of the cervical efferent vagus nerves of cats and dogs with measurement of pulmonary resistance (Rl) and anatomic dead space (Vd), and with anatomic study of rapidly frozen lungs. Stimulus frequencies between 1 and 12/sec produced almost the full range of Rl responses in eight cats. The major constrictor response to stimulation of one vagus nerve was in the lung of the same side in dogs and cats. A decrease of Vd assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1970
1970
2000
2000

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…It is likely that some of the tracheal or bronchial dilatation observed during sympathetic nerve stimulation in intact animals such as dogs (Olsen, Colebatch, Mebel, Nadel & Staub, 1965) or guinea-pigs (Yip et al 1981) is mediated by catecholamines released from perivascular nerves and diffusing into the airways muscle layer.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that some of the tracheal or bronchial dilatation observed during sympathetic nerve stimulation in intact animals such as dogs (Olsen, Colebatch, Mebel, Nadel & Staub, 1965) or guinea-pigs (Yip et al 1981) is mediated by catecholamines released from perivascular nerves and diffusing into the airways muscle layer.…”
Section: Discussionmentioning
confidence: 99%
“…15 16 Physiological function of cholinergic nerves in the airways Stimulation of the parasympathetic nerves releases acetylcholine which causes the airway smooth muscle to contract, [15][16][17][18][19] the glandular tissue to secrete mucus, 20 21 and the bronchial circulation to dilate. 22 23 Studies both in man and in animals have shown that, in addition to causing contraction, the vagus nerves also maintain a baseline tonic contraction of the airway smooth muscle.…”
Section: Cholinergic Receptors In the Airwaysmentioning
confidence: 99%
“…It was especially important to know whether muscarinic receptors influence parasympathetic nerve activity in cat lung because this species has been used for many of the definitive studies on the dominant role of parasympathetic reflexes in the control of airway smooth muscle, (Daly & Mount, 1951;Widdicombe, 1954ab;Nadel et al, 1971;Olsen et al, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…airway smooth muscle down to the level of the peripheral, respiratory bronchioles (Olsen et al, 1965;Nadel et al, 1971;Cabezas et al, 1971). In order to localize the neuronal muscarinic receptors within the airways, a method was chosen which recorded both lung resistance and dynamic lung compliance as these measurements reflect changes occurring mainly in the central and peripheral airways respectively (Widdicombe, 1963 Both vagi were tied and the distal ends stimulated simultaneously (10-20 V, 0.2 ms, 5-30 Hz, 300 pulses per train) at 5 min intervals with shielded platinium electrodes immersed in a pool of liquid paraffin.…”
Section: Introductionmentioning
confidence: 99%